2015
DOI: 10.1080/10494820.2015.1090456
|View full text |Cite
|
Sign up to set email alerts
|

How can students’ academic performance in statistics be improved? Testing the influence of social and temporal-self comparison feedback in a web-based training environment

Abstract: The aim of this study was to examine how social or temporal-self comparison feedback, delivered in real-time in a web-based training environment, could influence the academic performance of students in a statistics examination.First-year psychology students were given the opportunity to train for a statistics examination during a semester by doing online exercises in a web-based training environment. Once connected, students received in real-time either social comparison feedback (their score was compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…It is possible that, these types of negative study habits can be handled by using the curvilinear function of procrastination for exams. It can be a solution to send automatic reminders via e-mail in order to stimulate students' interest in taking part in the online exercises (Delaval et al, 2017). Yet, it is seen that it is not easy to overcome this behavior during the whole semester regularly for a couple of assignments for students in DL.…”
Section: Assignment Score Predictorsmentioning
confidence: 99%
“…It is possible that, these types of negative study habits can be handled by using the curvilinear function of procrastination for exams. It can be a solution to send automatic reminders via e-mail in order to stimulate students' interest in taking part in the online exercises (Delaval et al, 2017). Yet, it is seen that it is not easy to overcome this behavior during the whole semester regularly for a couple of assignments for students in DL.…”
Section: Assignment Score Predictorsmentioning
confidence: 99%
“…While some studies used online teaching interventions to meet the assessment needs of a course (such as Cordier et al, 2016;James, 2016;Nutan & Demps, 2014), other studies extended the online learning approach to encompass all aspects of teaching and learning (Curtis et al, 2013;Lewis & Sewell, 2007;North et al, 2018;Suleman, 2016). Some studies utilised online learning interventions as targeted strategies to achieve a single outcome as part of the course delivery, such as preparation for the final assessment (Delaval et al, 2017), while other studies used these strategies with a focus on promotion of discussions among the student cohort (Lin & Crawford, 2007). Some studies reported the development and evaluation of bespoke online teaching initiatives that tapped into technologies such as social media (Gagnon, 2015;McClean et al, 2016).…”
Section: Types Of Online Teaching Interventionsmentioning
confidence: 99%
“…Six of the 19 studies reported on the effect of the online intervention on measures of academic performance. Four of these studies involved online formative learning exercises performed in addition to other study strategies (Delaval et al, 2017;Sando & Feng, 2018;Soh et al, 2013;Stamper et al, 2017). Student performance was primarily assessed with multiple-choice questions (Delaval et al, 2017;Sando & Feng, 2018;Stamper et al, 2017), but Soh et al (2013) used eye-tracking software to investigate how students visually searched and detected abnormalities on a mammogram image.…”
Section: Student Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Naturalistic task interventions, such as scheduled daily writing tasks and random compliance checking (Boice, 1989), are more scalable, do not need highly trained therapists, and are often able to use more objective measures of task delay to quantify efficacy. However, studies evaluating these interventions are scarce and findings have been inconsistent, with recent examples producing mixed success in reducing procrastination (Ariely & Wertenbroch, 2002; Delaval, Michinov, Le Bohec, & Le Hénaff, 2015).…”
Section: Introductionmentioning
confidence: 99%